Esophageal Motility Disorders Associated With Death or Allograft Dysfunction After Lung Transplantation? Results of a Retrospective Monocentric Study - Gouynou, Célia; Philit, François; Mion, François; Tronc, François; Sénéchal, Agathe; Giai, Joris; Rabain, Anne-Marie; Mornex, Jean-François; Roman, Sabine (Clinical and translational gastroenterology, 2020)
Pathological gastroesophageal reflux (GER) is a known risk factor for bronchiolitis obliterans syndrome (BOS) after lung transplantation. This study aimed at determining whether functional esophageal evaluation might predict BOS occurrence and survival in this setting. Ninety-three patients who underwent esophageal high-resolution manometry and 24-hour pH-impedance monitoring within the first year after lung transplantation were retrospectively included. A univariable analysis was performed to evaluate the parameters associated with GER disease and BOS occurrence. The Cox regression model was used to identify the prognostic factors of death or retransplantation. Thirteen percent of patients exhibited major esophageal motility disorders and 20% pathological GER. GER occurrence was associated with younger age, cystic fibrosis, and hypotensive esophagogastric junction. Within a median follow-up of 62 months, 10 patients (11%) developed BOS, and no predictive factors were identified. At the end of the follow-up, 10 patients died and 1 underwent retransplantation. The 5-year cumulative survival rate without retransplantation was lower in patients with major esophageal motility disorders compared with that in those without (75% vs 90%, P = 0.01) and in patients who developed BOS compared with that in those without (66% vs 91%; P = 0.005). However, in multivariable analysis, major esophageal motility disorders and BOS were no longer significant predictors of survival without retransplantation. Major esophageal motility disorders and BOS were associated with allograft survival in lung transplantation in the univariable analysis. Although the causes of this association remain to be determined, this observation confirms that esophageal motor dysfunction should be evaluated in the context of lung transplantation.